2019
DOI: 10.4143/crt.2018.100
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of PITX2 Promotes Letrozole Resistance Via Transcriptional Activation of IFITM1 Signaling in Breast Cancer Cells

Abstract: These results demonstrate that constitutive upregulation of PITX2/IFITM1 cascade is an intrinsic adaptive mechanism during the pathogenesis of letrozole-resistance, and modulation of PITX2/IFITM1 level using different genetic and pharmacological means would thus have a novel therapeutic potential against letrozole resistance in BCa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…PITX2 shows a strong correlation with specific drug responses (e.g., doxorubicin and letrozole) in preclinical cancer models mediated by ABC type drug transporters, importers, and other pathways [22-24], which supports the role of PITX2 as a drug-specific response marker. This is also supported by our results, showing a HR of 5.71 in the subgroup treated with anthracycline without taxanes, compared to a HR of 3.96 in the overall anthracycline-treated group (including or not including taxanes in the therapy regimen).…”
Section: Discussionmentioning
confidence: 85%
“…PITX2 shows a strong correlation with specific drug responses (e.g., doxorubicin and letrozole) in preclinical cancer models mediated by ABC type drug transporters, importers, and other pathways [22-24], which supports the role of PITX2 as a drug-specific response marker. This is also supported by our results, showing a HR of 5.71 in the subgroup treated with anthracycline without taxanes, compared to a HR of 3.96 in the overall anthracycline-treated group (including or not including taxanes in the therapy regimen).…”
Section: Discussionmentioning
confidence: 85%
“…Recently, more and more studies show the critical role of PITX2 in many kinds of cancers. In breast cancer cells, upregulation of PITX2 promotes letrozole resistance via transcriptional activation of IFITM1 signaling [52]. The PITX2 DNA methylation was confirmed as a biomarker for the risk and prognosis of colorectal carcinoma [53], head and neck squamous cell carcinoma [54], urothelial bladder cancer [55] and prostate cancer [56].…”
Section: Discussionmentioning
confidence: 91%
“…It has been reported that PITX2 is involved in the development of several types of cancer [ 21 , 22 ]. A study demonstrated that the PITX2 upregulation could enhance the resistance of breast cancer cells to letrozole via activating the interferon‑induced transmembrane protein 1 pathway [ 23 ]. Another study revealed that microRNA-21 could enhanced the apoptosis and attenuate the proliferation of pituitary adenoma cells [ 24 ].…”
Section: Discussionmentioning
confidence: 99%